1995
DOI: 10.2527/1995.73123649x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of rate of lean tissue growth and other factors to concentration of urea in plasma of pigs.

Abstract: The objectives of this study were 1) to investigate the relationship between plasma urea N concentrations (PUN) and lean tissue growth and 2) to compare the value of different variables, related to lean growth and renal function, to correct the relationship between dietary lysine concentration and PUN response for variation not related to amino acid adequacy. Forty-eight gilts (64.8 kg BW) were individually penned (blocks based on initial BW) for 50 d: a 10-d adjustment, a 35-d pretreatment, and a 5-d treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 16 publications
3
42
0
3
Order By: Relevance
“…In our study, plasma TP, BUN concentration and lysozyme activity were not affected by the PP supplementation, which may be related to the absence of any effect of the PP mixture on growth performance. Blood BUN concentration was used to monitor the adequacy of dietary amino acids in growing animals and has been suggested as a potential indicator of efficiency of lean tissue growth in pigs (Coma et al, 1995). In our studies, although PP mixtures showed excellent inhibitory activity on bacterial growth in the laboratory, no antimicrobial activity occurred in the faeces or caecum content of piglets throughout the in vivo experimental period.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, plasma TP, BUN concentration and lysozyme activity were not affected by the PP supplementation, which may be related to the absence of any effect of the PP mixture on growth performance. Blood BUN concentration was used to monitor the adequacy of dietary amino acids in growing animals and has been suggested as a potential indicator of efficiency of lean tissue growth in pigs (Coma et al, 1995). In our studies, although PP mixtures showed excellent inhibitory activity on bacterial growth in the laboratory, no antimicrobial activity occurred in the faeces or caecum content of piglets throughout the in vivo experimental period.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, the better growth performance in piglets fed YP diet could be partially explained by the lower concentrations of serum amino acids and urea, which suggested that protein deposition was greater in piglets receiving YP diet. Particularly, urea is the main nitrogenous end product arising from the amino acids catabolism in mammals, systematic concentration of urea is inversely related to protein deposition and FCR (Coma et al 1995), the inadequacy or poor quality of dietary protein can increase serum concentration of urea (Shen et al 2011). In addition, urea concentration has been classically recognized as an indicator of renal function, the lower concentration of serum urea would alleviate the metabolic load of kidney (White et al 1991), which may explain why relative kidney weight in piglets fed YP diet was lower.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, blood urea N concentration can be inversely related to the efficiency of N utilization (Coma et al, 1995) and is associated with dietary protein intake (Yang et al, 2000). No difference in serum urea was found when Iberian and Landrace gilts fed isonitrogenous diets were compared, although serum urea was diminished when the animals were fed with lower CP diets (Fernández-Fígares et al, 2007).…”
Section: I/g Ratiomentioning
confidence: 99%